1995
DOI: 10.1128/jb.177.7.1872-1878.1995
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of duplicate lysyl-tRNA synthetase gene homologs in Escherichia coli and other procaryotes

Abstract: The lysyl-tRNA synthetase (LysRS) system of Escherichia coli K-12 consists of two genes, lysS, which is constitutive, and lysU, which is inducible. It is of importance to know how extensively the two-gene LysRS system is distributed in procaryotes, in particular, among members of the family Enterobacteriaceae. To this end, the enterics E. coli K-12 and B; E. coli reference collection (ECOR) isolates EC2, EC49, EC65, and EC68; Shigella flexneri; Salmonella typhimurium; Klebsiella pneumoniae; Enterobacter aeroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…It appears then that E. coli encodes three lysyl-tRNA synthetases, LysS, LysU, and GenX. Although the lysS gene has been mapped at 66.2 min on the Salmonella chromosome, a location similar to that of the E. coli counterpart (12), the lysU gene is absent from the Salmonella genome (39). To our knowledge, this is the first report showing that PoxA is the second putative lysyl-tRNA synthetase in Salmonella (the first being LysS) and that genX and poxA are allelic.…”
Section: Discussionmentioning
confidence: 99%
“…It appears then that E. coli encodes three lysyl-tRNA synthetases, LysS, LysU, and GenX. Although the lysS gene has been mapped at 66.2 min on the Salmonella chromosome, a location similar to that of the E. coli counterpart (12), the lysU gene is absent from the Salmonella genome (39). To our knowledge, this is the first report showing that PoxA is the second putative lysyl-tRNA synthetase in Salmonella (the first being LysS) and that genX and poxA are allelic.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in keeping with that of Martinez and Mirande (49), who found that the N-terminal extension (amino acids 1 to 69) of S. cerevisiae LysRS was dispensable in vivo for aminoacylation activities. Furthermore, structural data from the E. coli LysRS S protein indicated that deletion of the N-terminal 30 amino acids (corresponding to amino acids 64 to 93 of human LysRS by sequence comparison) did not affect the ability of the protein to specifically recognize the anticodon loop of tRNA Lys and catalyze aminoacylation (9,58). Several highly conserved residues that are thought to be involved in binding to Mg 2ϩ and ATP have been identified in class II aminoacyl synthetases (to which LysRS belongs) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplication is a way to amplify production of a gene product or to ensure the synthesis of an essential, multifunctional protein. Expression of both msa1 and msa2 may be (21,37). While both copies of msa have identical sequences up to 40 bp upstream of the ORF, the sequences beyond are quite divergent.…”
Section: Discussionmentioning
confidence: 99%